The application of gargle containing honeysuckle and semen oroxyli to reduce the pain and complications after uvulopalatopharyngoplasty - Ren, Lihua; Li, Jun; Miao, Zhongyi; Yan, Ru; Li, Qunzhen; Zhang, Rong; Rong, Ting; Dong, Xuena (Frontiers in Pharmacology, 2022)
Purpose: The main purpose of this pilot study was to detect the positive effects of our self-made gargle containing honeysuckle and semen oroxyli on post-operative pain and complications after Uvulopalatopharyngoplasty (UPPP). Methods: Patients with obstructive sleep apnea (OSA) who had underwent elective UPPP during the period of April 2019 to January 2022 were randomly divided into treatment group and control group. The patients in the treatment group were instructed to gargle the solution containing honeysuckle and semen oroxyli (25 mL) four times a day for 2 weeks. The patients in the control group were instructed to gargle normal saline (25 mL) at the same schedule. The post-operative resting throat pain, swallowing throat pain and patient comfort level were evaluated at 12 hours, 1 week and 2 weeks after UPPP. The post-operative complications were collected and analyzed. Results: During the study period, 218 patients completed all the post-operative assessments. For resting throat pain, the treatment group had much lower VAS scores at 1 week and 2 weeks after UPPP. For swallowing throat pain, treatment group had much lower VAS scores than control group at 2 weeks after surgery. And patients in the treatment group felt more comfortable comparing to those in control group at 1 week and 2 weeks after UPPP. Although the treatment group had less numbers of patients with post-operative wound infection or bleeding, the difference between the 2 groups was not statistically significant. Conclusions: The gargle containing honeysuckle and semen oroxyli could relieve both resting and swallowing throat pain and increase patient comfort after UPPP.